Faktor-Faktor yang Mempengaruhi Kejadian Stunting pada Anak: Studi Literatur - Slamet Ali Mashar; Suhartono Suhartono; Budiono Budiono (Fakultas Teknik, 2021)
Stunting is a global health problem and in Indonesia, both in urban and rural areas. Stunting occurs in children and if preventive actions are not taken such as nutrition, immunization, and maintain a clean environment, it may cause disturbances in children in brain development, body metabolism, and physical growth. Risk factors for stunting in children’s parental habits , basic immunization, basic sanitation, history of infectious diseases, smoking habits, and upper respiratory tract infections. The purpose of this study is to provide information on factors that play a role in the risk of stunting according to a review study. This study uses a descriptive method with a literature review approach using previous research from the Sinta database. The review criteria used are indexed by Sinta 2, 3, 4, and 5, published times over the last 5 years. The conclusion of this literature review study is that there are several factors associated with the incidence of stunting such as the parenting habits of children, basic immunization, basic sanitation, history of infectious diseases, smoking habits, and incidence of respiratory infections.